2018
DOI: 10.1080/01490451.2018.1443170
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Redox Potential Control to Improve the Efficiency of Chalcopyrite Bioleaching

Abstract: The effect of controlling the redox potential (Eh) on chalcopyrite bioleaching kinetics was studied as a new aspect of redox control during chalcopyrite bioleaching, and its mechanism was investigated by employing the "normalized" solution redox potential (Enormal) and the reaction kinetics model. Different Eh ranges were established by use of different acidophiles (Sulfobacillus acidophilus YTF1; Sulfobacillus sibiricus N1; Acidimicrobium ferrooxidans ICP; Acidiplasma sp. Fv-AP). Cu dissolution was very susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 43 publications
1
18
1
Order By: Relevance
“…As dissolution of pure chalcopyrite is theoretically characterized by a 1:1 ratio of released iron to copper, this confirms the preferential oxidation of this copper mineral, or the transiently produced chalcocite, over associated copper-deficient minerals, such as pyrite, at low redox potentials. Our data independently confirms a study by Masaki et al (2018), in which microbial redox control was also attempted, likewise by members of the Sulfobacilli, i.e., S. sibiricus and S. acidophilus . Using iron-oxidizing bacteria in bioleaching processes, which raise the ORP only minimally over the threshold for the onset of leaching therefore appears possible and could benefit the performance of chalcopyrite bioleaching processes.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…As dissolution of pure chalcopyrite is theoretically characterized by a 1:1 ratio of released iron to copper, this confirms the preferential oxidation of this copper mineral, or the transiently produced chalcocite, over associated copper-deficient minerals, such as pyrite, at low redox potentials. Our data independently confirms a study by Masaki et al (2018), in which microbial redox control was also attempted, likewise by members of the Sulfobacilli, i.e., S. sibiricus and S. acidophilus . Using iron-oxidizing bacteria in bioleaching processes, which raise the ORP only minimally over the threshold for the onset of leaching therefore appears possible and could benefit the performance of chalcopyrite bioleaching processes.…”
Section: Resultssupporting
confidence: 90%
“…Consequently, ferric ions diluted in the bulk medium maintain a more homogeneous redox environment. Unfortunately, Masaki et al (2018) did not report on attachment rates and this hypothesis remains to be tested.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The problems associated with chalcopyrite bioleaching (i.e., when the target metal forms part of the mineral matrix) are slow rates and poor total recoveries often attributed to passivation of the mineral surface that has recently (2020) 7:215 | https://doi.org/10.1038/s41597-020-0519-2 www.nature.com/scientificdata www.nature.com/scientificdata/ been suggested to be by iron-oxyhydroxides 6 . One method to avoid chalcopyrite passivation is to carry out the bioleaching at low redox potentials and high temperatures 7,8 and several methods have been suggested to maintain the redox potential in the desired range including controlling the oxygen concentration 9 or utilizing a microbial community that maintains the potential in the desired range 10,11 . An additional critical factor for chalcopyrite bioleaching, especially in early stages of bioheap inoculation, is the attachment and biofilm formation on the mineral surface 12 .…”
Section: Background and Summarymentioning
confidence: 99%
“…In the case of bioleaching studies of chalcopyrite, Gericke et al [15] and Ahmadi et al [16,17] reported the advantages of E h control (via electrochemical reduction or oxygen arrest) at 600-650 mV (SHE), owing to the suppression of pyrite oxidation and thereby preventing jarosite passivation. These were followed by our E h -controlled bioleaching study using "weak" Fe 2+ -oxidizing microorganisms [18]. Masaki et al [18] reported the reaction ratelimiting step being dependent on E h and successfully clarified the chalcopyrite bioleaching efficiency by incorporating the concept of E normal : Controlling the optimal E h level to satisfy 0 ≤ E normal ≤ 1 (especially at E normal = ~0.35 at 45 • C) was critical in promoting steady Cu solubilization by a surface chemical reaction.…”
Section: Introductionmentioning
confidence: 99%